2014
DOI: 10.1093/carcin/bgu139
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin-like 1 promotes invadopodia formation and metastasis through activation of Rac1/Cdc42/cortactin signaling in breast cancer cells

Abstract: Metastatic disease is the leading cause of cancer mortality. Identifying biomarkers and regulatory mechanisms is important toward developing diagnostic and therapeutic tools against metastatic cancer. In this study, we demonstrated that podocalyxin-like 1 (PODXL) is overexpressed in breast tumor cells and increased in lymph node metastatic cancer. Mechanistically, we found that the expression of PODXL was associated with cell motility and invasiveness. Suppression of PODXL in MDA-MB-231 cells reduced lamellipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 45 publications
7
61
0
Order By: Relevance
“…It was reported that lower miR-142 expression in hepatocellular carcinoma was significantly associated with poor survival (17). Rac1 expression is frequently upregulated in several types of cancers, including hepatic cancer (14) and breast cancer (20). In line with previous studies, in the present study, we also found that miR-142 was downregulated, while Rac1 was upregulated in 6 osteosarcoma tissue samples compared with the paired normal bone tissues.…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that lower miR-142 expression in hepatocellular carcinoma was significantly associated with poor survival (17). Rac1 expression is frequently upregulated in several types of cancers, including hepatic cancer (14) and breast cancer (20). In line with previous studies, in the present study, we also found that miR-142 was downregulated, while Rac1 was upregulated in 6 osteosarcoma tissue samples compared with the paired normal bone tissues.…”
Section: Discussionsupporting
confidence: 91%
“…hsu et al reported PODXL-ebP50-ezrin molecular complex enhances the metastatic potential of renal cancer through recruiting RAC1 guanine nucleotide exchange factor, ARhgeF7 (60). Lin et al reported that PODXL promotes invadopodia formation and metastasis through activation of RAC1-Cdc42-cortactin signaling in breast cancer cells (61) and it is thought to regulate cell adhesion through its connections to intracellular proteins and to extracellular ligands (31)(32)(33)(34)(35). In our study, the adhesion capability of MS cells that showed high PODXL expression was remarkably decreased compared with that of low PODXL-expressing cells, as previously reported (31)(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 86%
“…Studies from diverse types of cancers have suggested the essential role of Rac1 in regulating tumor metastasis. Rac1 can be activated by multiple upstream signals and induce invadopodia formation and cause metastasis in breast cancer (15). Activated Rac1 promotes the assembly of cell surface integrin protein molecules in the surface of the head of the cells and passes regulative signals to the actin cytoskeleton, thus, inducing actin filaments to aggregate in the plasma membrane and form sheets of pseudopodia, leading to cell membrane multipolarization, which eventually affects the movement of cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Although Rac1 as a cytoskeleton organizer has been documented well, more and more recent findings provoked broad functions of Rac1 in human cancers. Rac1 regulates a diverse spectrum of cellular functions including tumorigenesis (11), angiogenesis (12,13) and metastasis (11,14,15). Overexpression of Rac1 occurs in several different types of tumors including breast (16,17), colon (18), bladder (19), and gastric cancer (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation